ECONOMIC ACTIVITY OF MICROFINANCE ORGANIZATIONS AND THEIR ROLE IN THE DEVELOPMENT OF SMALL BUSINESSES - Madaminova , Nargiza Ibadullayevna (Educational Research in Universal Sciences, 2023)
This article highlights the importance of microfinance organizations and their importance in the financial support of small businesses and entrepreneurial activities, modern manifestations of lending to entrepreneurial entities by microfinance organizations and their inherent trends. Microfinance organizations have also developed practical recommendations for identifying deficiencies in the financing of business entities in the development of the services market and their elimination.